Blautia massiliensis sp. nov., isolated from a fresh human fecal sample and emended description of the genus Blautia. (February 2017) - Durand, Guillaume A.; Pham, Thao; Ndongo, Sokhna; Traore, Sory Ibrahima; Dubourg, Grégory; Lagier, Jean-Christophe; Michelle, Caroline; Armstrong, Nicholas; Fournier, Pierre-Edouard; Raoult, Didier; Million, Matthieu
Abstract: The strain GD9 T is the type strain of the newly proposed species Blautia massiliensis sp. nov., belonging to the family Lachnospiraceae . It was isolated from a fresh stool sample collected from a healthy human using the culturomics strategy. Cells are Gram-negative rods, oxygen intolerant, non-motile and non-spore forming. The 16S rRNA gene sequencing showed that strain GD9 T was closely related to Blautia luti, with a 97.8% sequence similarity. Major fatty acids were C14:0 (19.8%) and C16:0 (53.2%). Strain GD9 T exhibits a genome of 3, 717, 339 bp that contains 3, 346 protein-coding genes and 81 RNAs genes including 63 tRNAs. The features of this organism are described here, with its complete genome sequence and annotation. Compared with other Blautia species which are Gram positive, the strain was Gram negative justifying an emended description of the genus Blautia . Highlights: Proposal of the new species Blautia massiliensis using taxonogenomics Type strain GD9 T was isolated in Marseille from healthy human gut using culturomics. B. massiliensis is found in 41% of 16, 667 human gut metagenomes. B. massiliensis is as abundant as 27% of total reads of a human gut metagenome. B. massiliensis is probably an important member of the human gut microbiota.